Preoperative PROMIS Physical Function Scores Predict Postoperative Outcomes Following Total Ankle Replacement - Matthew S. Conti MD; Kristin C. Caolo BA; Agnes D. Cororaton MS; Jonathan T. Deland MD; Constantine A. Demetracopoulos MD; Scott J. Ellis MD (Foot & Ankle Orthopaedics, 2021)
Background: Despite good evidence that supports significant improvements in pain and physical function following a total ankle replacement (TAR) for end-stage ankle arthritis, there is a subset of patients who do not significantly benefit from surgery. The purpose of this study was to perform a preliminary analysis to determine if preoperative Patient-Reported Outcome Measurement Information System (PROMIS) scores could be used to predict which patients were at risk of not meaningfully improving following a TAR. Methods: Prospectively collected preoperative and ≥2-year postoperative PROMIS physical function, pain interference, pain intensity, and depression scores for 111 feet in 105 patients were included in the study. Significant postoperative improvement was defined using minimal clinically important differences (MCIDs). Logistic regression models and area under the curve (AUC) analyses were used to determine whether preoperative PROMIS scores were predictive of postoperative outcomes. Results: Receiver operating characteristic curves found statistically significant AUCs for the PROMIS physical function (AUC = 0.728, P = .004), pain intensity (AUC = 0.720, P = .018), and depression (AUC = 0.761, P < .001) domains. The preoperative PROMIS pain interference domain did not achieve a statistically significant AUC. Conclusion: Preoperative PROMIS physical function and pain intensity t scores may be used to predict postoperative improvement in patients following a fixed-bearing TAR; however, preoperative PROMIS pain interference scores were not good predictors. The results of this study may be used to guide research regarding patient-reported outcomes following TAR. Level of Evidence: Level III, retrospective comparative series.